CLASSIFICATION AND REGRESSION TREE (CART) DALAM KLASIFIKASI KEMANDIRIAN HIDUP BERDASARKAN KONDISI KESEHATAN LANSIA DI KELURAHAN KASIN WILAYAH KERJA PUSKESMAS BARENG KOTA MALANG - Wisoedhanie Widi Anugrahanti; Oda Debora; Berliany Venny Sipollo (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2019)
Backgraund: The elderly must be able to adapt to all the changes that occur in their lives. The ability of the elderly to adapt to life changes can help reduce the Dependency Ratio. Dependency Ratio can be minimized through achieving the independence of life of the elderly. Health condition is one of the factors that is closely related to the ability of the elderly to live independently in their old age. Aim : This study aims to identify the elderly in the independence of their lives in Kelurahan Kasin Peripheral Hospital of Bareng Malang, through the health condition approach Method: Based on the time of this study, it is classified as cross-sectional with elderly respondents aged 60 years and over in Kasin Kelurahan, a total of 142 obtained through the multistage random sampling. The instruments used were IADL, sphygmomanometer, Snellen test, Abbreviated Mentaltest (AMT), Geriatric Depression Scale (GDS), along with questionnaires to identify conditions and the perception of the elderly towards their health conditions. CART is used for the classification of independence of the elderly with the Salfold Predictive Modeller software Results: The classification results showed that 78.2% of the elderly were independent, characterized by having a certain daily diet, having normal hearing function or having an impairment, having better health perception, having musculoskeletal disorders, and not taking drugs. The best sorting based on the value of goodness of split is the daily menu consumed by the elderly 0.1125041, current health perception 0.0813413, hearing function 0.0652887, musculoskeletal disorders 0.0204411, drug consumption 0.0002492. The accuracy value obtained is 69.72%, sensitivity value is 71.17% and specificity value is 64.52% Conclusion :Daily menu consumed by the elderly and current perception of health are variables that contribute to the independence of the elderly based on health conditions, while the use of stairs, daily physical activity, home improvement is a functional capacity that contributes to the independence of the elderly.